Climate change and agroecology: directions for sustainable agriculture - Vitória , Tayná de Oliveira; Santos, Rosângela Leal (Technical and Scientific Journal Green Cities, 2025)
The objective of this work is to propose the implementation of the 6 concepts of Tropical Agroecology as a tool for agricultural socioeconomic development in Brazil, concomitant with the protection of natural resources, adaptation and mitigation of climate change. For this purpose, maps and a table of land use and land cover were prepared in the Northeast Region of Brazil in the years 2000, 2010 and 2020 – based on data from Collection 8 of MAPBIOMAS BRASIL; in order to observe the evolution of land uses and covers over these 20 years, a period in which most of these lands have been cultivated in a predatory manner. It could be observed that in the aforementioned period of time, 9,301,129 hectares of Forest were eliminated while agriculture had an increase of 9,065,853 hectares, in the same period of time. This inversely proportional relationship between vegetation and agriculture – which is a pattern of traditional and predatory agriculture on natural resources – is one of the constants that has contributed to climate change in the country. In this way, it is necessary to implement the 6 concepts of Tropical Agroecology since from them, there is the possibility of reconciling agricultural socioeconomic development with the minimum possible ecological footprint, since Agroecology works in a systemic and holistic way with ecosystems, the crop field being an ecosystem.
Keywords: Sustainability; Management; Natural resources